Experiences, perceptions and ethical considerations of the malaria infection study in Thailand - Bhensri Naemiratch; Natinee Kulpijit; Supanat Ruangkajorn; Nicholas P. J. Day; Jetsumon Prachumsri; Phaik Yeong Cheah (BMC Medical Ethics)
Abstract Background Thailand has made significant progress in malaria control efforts in the past decade, with a decline in the number of reported cases. However, due to cross-border movements over the past 5 years, reported malaria cases in Thailand have risen. The Malaria Infection Study in Thailand (MIST) involves deliberate infection of healthy volunteers with Plasmodium vivax malaria parasites, and the assessment of the efficacy of potential vaccine and drug candidates in order to understand acquired protection against malaria parasites. Methods This paper drew from ethics and social science qualitative study called MIST-ETHICS embedded within the MIST studies. MIST-ETHICS aimed to describe and understand the experiences, perceptions and ethical considerations of the MIST studies. Data were obtained from semi-structured interviews and a focus group discussion. A total of 46 participants participated in MIST-ETHICS . Results Three major themes emerged: experiences and perceptions of MIST, reasons for joining MIST, and ethical considerations. We found that although compensation was a motivation for participation, this was secondary to it being beneficial to self (health checks; link to health networks; building merit) and others (medical research contribution; altruism). Participants expressed varied opinions regarding the requirement of a university degree as one of the inclusion criteria for MIST. Conclusions Our study revealed widespread concerns about long-term health effects and safety. Ethical considerations, including obtaining valid informed consent and ensuring participant inclusivitiy, were deem essential. Despite some debate regarding eligibility criteria, most participants agreed that the informed consent process was robust, accompanied by a strong sense of responsibility to contribute to the greater good. We emphasize the importance of continuously gathering participants’ feedback for quality control, such as improving information materials to clarify the purpose of initial phases, their contributing to later phases, and the rationale behind each selection criterion. Trial registration This manuscript is part of the clinical trials registered under ClinicalTrials.gov IDs NCT04083508 (MIST1) registered on 5 Sep 2019 and NCT05071079 (MIST2) registered on 28 July 2021. However, the manuscript pertains to a qualitative study that does not require trial registration.